2018
DOI: 10.3390/s18040934
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vibration Characteristics on the Atomization Rate in a Micro-Tapered Aperture Atomizer

Abstract: Because little is known about the atomization theory of a micro-tapered aperture atomizer, we investigated the vibration characteristics of this type of atomizer. The atomization mechanism of a micro-tapered aperture atomizer was described, and the atomization rate equation was deduced. As observed via microscopy, the angle of the micro-tapered aperture changes with the applied voltage, which proved the existence of a dynamic cone angle. The forward and reverse atomization rates were measured at various voltag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The volume of the cone apertures changes is follows [42]: Olsson [45] compared the results obtained from the numerical calculation for conical flows and those mentioned in reference [46] and found that the flow resistances in the nozzle/diffuser elements at the micro-scale are similar to those at the macro-scale. Therefore, in this study, the flow resistances in the nozzle/diffuser elements at the micro-cone hole can use the empirical curves in Figure 4.…”
Section: Atomization Ratementioning
confidence: 97%
See 3 more Smart Citations
“…The volume of the cone apertures changes is follows [42]: Olsson [45] compared the results obtained from the numerical calculation for conical flows and those mentioned in reference [46] and found that the flow resistances in the nozzle/diffuser elements at the micro-scale are similar to those at the macro-scale. Therefore, in this study, the flow resistances in the nozzle/diffuser elements at the micro-cone hole can use the empirical curves in Figure 4.…”
Section: Atomization Ratementioning
confidence: 97%
“…Figure 3 shows the illustrative diagram of the dynamic cone angle. We have analyzed the theory of the dynamic cone angle [42,43]. Figure 3 shows the illustrative diagram of the dynamic cone angle.…”
Section: Structure Of the Ultrasonic Atomizer And Micro-cone Holementioning
confidence: 99%
See 2 more Smart Citations
“…Sci. 2019, 9, According to the relationship between volume change, flow rate and frequency [43,44], the flow rate equation of the SLFT PZT pump is…”
Section: Flow Field Simulationmentioning
confidence: 99%